Detecting and phasing minor single-nucleotide variants from long-read sequencing data - Zhixing Feng (Nature Portfolio, 2021)
Cellular genetic heterogeneity is common across biological conditions, yet application of long-read sequencing to this subject is limited by error rates. Here, the authors present iGDA, a tool for detection and phasing of minor variants from long-read sequencing data, allowing accurate reconstruction of haplotypes.